MO018: The Need for Routine Native Nephrectomy in the Work-Up for a Kidney Transplantation in Autosomal Dominant Polycystic Kidney Disease Patients. (3rd May 2022) - Geertsema, Paul; Gansevoort, Ronald; Koorevaar, Iris; Leliveld-Kors, Annemarie; Meijer, Esther; Pol, Robert; Sanders, Jan-Stephan; Casteleijn, Niek F
Abstract: BACKGROUND AND AIMS: In some patients with autosomal dominant polycystic kidney disease (ADPKD), one or both native kidneys are removed in the work-up for kidney transplantation. There is no consensus if and when a nephrectomy should be performed. Some centers advocate to routinely perform a (bilateral) nephrectomy to prevent complications associated with the native polycystic kidneys in the post-transplantation period. In our ADPKD expertise center, a restrictive approach is pursued: a nephrectomy is only performed in case of serious volume related complaints, lack of space for the allograft, recurrent cyst infections, persistent cyst bleedings or chronic invalidating pain. We analyzed in a retrospective study whether this approach is justified. METHOD: All records of patients ≥18 years with ADPKD who received a kidney transplantation (Tx) in our ADPKD expertise center between January 2000 and January 2019 were reviewed. Data were collected on incidence, timing, indication and complications of nephrectomy, as well as on the kidney transplantation, graft function and mortality. Patients were subdivided into three groups: no nephrectomy (no-Nx), nephrectomy prior to (pre-Tx) or after kidney transplantation (post-Tx). Patients were followed for at least 12 months after transplantation. RESULTS: About 391 ADPKD (54 ± 9 years, 55.2% male) patients were included. The majority of patients did not undergo a nephrectomy ( n = 257, 65.7%). A unilateral nephrectomy was performed pre-Tx in 114 patients (29.2%), in most cases because of a lack of space (49.6%) or recurrent kidney cyst infection (28.1%). More male patients underwent a nephrectomy compared to women (65.7% versus 34.3%, P = 0.003). After Tx, nephrectomy was performed in only 30 patients (11%, median 4.4 years post-Tx), of which 10 were contralateral nephrectomies in patients who also had a nephrectomy pre-Tx. Most frequent indications for nephrectomy post-Tx were recurrent kidney cyst infection (51.4%) or severe pain (24.3%). Duration of nephrectomy was slightly longer when performed post-Tx (3.1 h post-Tx versus 2.6 h pre-Tx, P = 0.052). However, the median length of hospital admission was significantly shorter in these patients (6.0 days post-Tx versus 10.0 days pre-Tx, P < 0.001). Surgery related complication rates did not differ between both groups (38.3% pre-Tx versus 27.0% post-Tx, P = 0.3), nor were there any differences in 10-year patient survival (74.4% pre-Tx versus 80.7% post-Tx versus 67.6% no-Nx, P = 0.4), or 10-year death-censored graft survival (84.4% pre-Tx versus 85.5% post-Tx versus 90.0% no-Nx, P = 0.9). CONCLUSION: This study indicates that a minority of ADPKD patients require a native nephrectomy in the work-up for a kidney transplant. With a restrictive nephrectomy policy, only few patients need a nephrectomy after kidney transplantation for indications not foreseen before transplantation. Nephrectomy is a relatively safe procedure, even when performed in transplanted ADPKD patients where it did not result in more complications, graft failure or mortality. These data suggest that a restrictive nephrectomy policy in ADPKD is justified.